2011
DOI: 10.1111/j.1365-2982.2011.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow gallbladder emptying reverts to normal but small intestinal transit of a physiological meal remains slow in celiac patients during gluten‐free diet

Abstract: Slow postprandial MCTT in response to a physiological meal does not revert to normal during GFD, an effect mirroring incomplete histopathologic recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The authors demonstrated that patients with CD and fat malabsorption tend to have a delayed mouth-cecum transit in spite of apparently normal gastric emptying and normal levels of insulin, GIP, CCC, neurotensin and PYY [12]. A delay in M-CTT in CD was also reported by Benini et al [29]. …”
Section: Gastrointestinal Motility Alterations In CD and Ncgsmentioning
confidence: 86%
See 4 more Smart Citations
“…The authors demonstrated that patients with CD and fat malabsorption tend to have a delayed mouth-cecum transit in spite of apparently normal gastric emptying and normal levels of insulin, GIP, CCC, neurotensin and PYY [12]. A delay in M-CTT in CD was also reported by Benini et al [29]. …”
Section: Gastrointestinal Motility Alterations In CD and Ncgsmentioning
confidence: 86%
“…A positive effect of the GFD on M-CTT was reported by some groups, but not confirmed by others [29]. In a study performed by Bassotti et al [31], motility alterations assessed by manometry persisted on those in whom CD was still active, despite the GFD.…”
Section: The Effect Of Gfd On Gut Motilitymentioning
confidence: 87%
See 3 more Smart Citations